2011
DOI: 10.2174/157018011794578222
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Warfarins Pharmacologic Properties in Clathrates with Glycyrrhizic Acid and Arabinogalactan

Abstract: The article describes the pharmacological examinations of clathrates of warfarin (WF) with glycyrrhizic acid (GA) and arabinogalactan (AG). A direct connection between the clathrate structure and the pharmacon's anticoagulative properties was observed. A 20 mg/kg (WF 2 mg/kg) dose of WF: GA 1:10 clathrate causes the increase in prothrombin time (PT) only in 54 hours, after 3 administrations. In contrast, a 20 mg/kg (WF 2 mg/kg) dose of WF: AG 1:10 clathrate leads to an increase in PT in 24 and 48 hours after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The complex formation was confirmed by differential scanning calorimetry and increased aqueous solubility of WF [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex formation was confirmed by differential scanning calorimetry and increased aqueous solubility of WF [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of these successful examples is water-soluble AG complex with warfarin, which is widely used as an indirect oral anticoagulant prescribed for a long time to patients with different cardiovascular diseases and after complicated surgeries [ 7 , 8 ]. The new complex was found to be highly effective; however, its anticoagulant activity was not as sharp as that of warfarin [ 9 ]. These data suggested that the complex is safer as compared to blank warfarin, since smoother blood dilution can reduce the risk of bleeding, which is one of the major side effects of warfarin [ 7 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ozonolytic cleavage of the cycloalkenyl C¼C bond in tetrahydroquinoline fused with cyclopentene affords the ozonides of aza-heterocycles [10]. To improve antimalaria or antiviral activity of synthetic peroxides and ozonides, their conjugates containing weakly basic functional groups and heterocycles were obtained [11].…”
Section: -Arylmentioning
confidence: 99%
“…This method opens a simple route to the synthesis of substituted tetrahydroquinolines [9].Ozonolytic cleavage of the cycloalkenyl C¼C bond in tetrahydroquinoline fused with cyclopentene affords the ozonides of aza-heterocycles [10]. To improve antimalaria or antiviral activity of synthetic peroxides and ozonides, their conjugates containing weakly basic functional groups and heterocycles were obtained [11].Within this context, we report here a one-pot three-component cyclocondensation of 4-fluoroaniline with aromatic aldehydes and cyclopentadiene to synthesize 6fluorotetrahydroquinoline annulated with cyclopentene for the following possibility to obtain their stable ozonides.…”
mentioning
confidence: 99%
“…Table 1 below shows solubility data reported in [22][23][24][25][26][27][28][29][30][31][32] as far as published for the first time in this review.…”
Section: Synthesis Of Supramolecular Systems Of Water-soluble Polysacmentioning
confidence: 99%